2018
DOI: 10.1111/tesg.12345
|View full text |Cite
|
Sign up to set email alerts
|

Proximity Matters: Inter‐Regional Knowledge Spillovers and Regional Industrial Diversification in China

Abstract: The effects of knowledge spillovers from neighbouring regions on regional industrial diversification should not be overlooked. Here we are referring to not only intra-industry knowledge spillovers from neighbouring regions, but also the spread of knowledge from related industries in neighbouring regions. This paper also develops an analytical framework that pays more attention to the role of institutional proximity between regions and how it is associated with geographical and cognitive proximity, and acknowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…At the regional level, Acemoglu et al (2015) found that spillover effects are sizable, accounting for about 50% of the quantitative impact of an expansion in the local state capacity. By analysing China's custom data, He et al (2019) found that knowledge spillovers play an important role in industrial diversification, and spillovers are more efficient if two regions have larger institutional proximity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the regional level, Acemoglu et al (2015) found that spillover effects are sizable, accounting for about 50% of the quantitative impact of an expansion in the local state capacity. By analysing China's custom data, He et al (2019) found that knowledge spillovers play an important role in industrial diversification, and spillovers are more efficient if two regions have larger institutional proximity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Industrial dynamics can be seen as a process of new industry creation, industrial evolution and growth, and decline of industry (Malerba, 2007). Since the main goal of the AAR and the establishment of AACs is to attract new firms and new industries, we only study new industry creation here, which has also been the focus of a large body of literature (Boschma & Capone, 2016; Boschma et al., 2013; Buenstorf et al., 2015; He et al., 2019). Our findings suggest that the establishment of AACs has a positive effect on new industry creation.…”
Section: Introductionmentioning
confidence: 99%
“…The path of regional industrial dynamics thus has been a key issue in economic geography and regional studies (Isaksen, 2014). A large body of literature has attributed regional economic development and regional industrial dynamics to various region-specific assets: firm agency (Simmie, 2012), institutional context (Dawley, 2014), local social contexts (Martin, 2010), local and trans-local knowledge spillovers (He et al, 2019), innovation and R&D activities (Lin et al, 2011), and environmental regulations (Ambec et al, 2013;Bommer, 1999).…”
mentioning
confidence: 99%
“…(2017), He et al. (2019), and Alonso and Martín (2019) find that spatial spillover between neighbor regions is a significant driving force for industrial evolution. In particular, with the rising economic complexity and increasing dependence of industrial evolution on the spatial network of collaboration, inter‐regional collective learning through regional interaction has become a major avenue for enhancing regional development.…”
Section: Introductionmentioning
confidence: 98%
“…A vast body of evidence has generally confirmed that spatial spillover, an important opportunity window to promote the evolution of local industries, has a positive impact on regional development. Boschma et al (2017), He et al (2019), and Alonso and Martín (2019) find that spatial spillover between neighbor regions is a significant driving force for industrial evolution. In particular, with the rising economic complexity and increasing dependence of industrial evolution on the spatial network of collaboration, inter-regional collective learning through regional interaction has become a major avenue for enhancing regional development.…”
Section: Introductionmentioning
confidence: 99%